Passengers' perception of air companies : the case of Southeast Asia-Europe air route - Khan, Md. Lutfar Rahman; Oudheusden, Dirk L. Van; Clarke Harry R.; Tabucanon, Mario T.; The Royal Government of The Netherlands (Bangkok : Asian Institute of Technology, 1981)
A simple method for investigating the attitude of air travelers toward the airlines has bee n studied. Nineteen airlines which fly, without change of airplane during the journey, between Bangkok and at least one European city were considered. Bangkok. was taken to represent the South-East Asian cities. A sample survey was conducted with personal interviews aided by a preset questionnaire. Singapore Airlines and Thai International emerged as the two most popular air companies serving this route, while Aeroflot was found to be the l east preferred. On the question of why passengers prefer one airline to another, it was found that 'Quality of food' , 'Puncuality' and 'Politeness of airline staff' were the most important attributes of the air companies. 'safety' and 'Fare' were not found to be important f or influencing travelers' preference. Geometric representations of the air companies were done on the basis o f the degrees of satisfaction provided by the air companies on the most important attributes. The representations were seen to be extremely helpful in revealing the present state of affairs regarding airline preference. It was observed that the South-East Asian airlines succeeded mainly because of their courteous service while the success of the reputed West European airlines was due t o their mechanical type of efficiency like offering a punctual service. The air companies were clustered using p-median clustering problem and the method worked quite well.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering. School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Consumers' preferences -- Europe; Consumers' preferences -- Asia, Southeastern; Air travel